Effects of Dengzhan Shengmai Capsule combined with butylphthalide soft capsule on oxidative stress indexes and serum Hcy and CRP levels in patients with vascular dementia - Ma, Yan; Sun, Wenping (Cellular and Molecular Biology, 2020)
This experiment was aimed to investigate the effect of Dengzhan Shengmai capsule combined with butylphthalide soft capsule on oxidative stress indexes and serum homocysteine (Hcy) and C-reactive protein (CRP) levels in patients with vascular dementia (VD). From July 2017 to July 2019, 123 patients with VD in our hospital were selected as the research object, and each patient was assigned a random number according to the order of treatment. Among them, No. 1 to 41 were the control group A, No. 42 to 82 were the control group B, and No. 83 to 123 were the research group. Control group A was given butylphthalide soft capsules, control group B was Dengzhanshengmai capsules, and the research group was given Dengzhanshengmai capsules combined with butylphthalide softgels. Comparison of clinical efficacy, the incidence of adverse reactions, and improvement of symptoms [Montreal Cognitive Assessment Scale (MocA) score, Vascular Dementia TCM Syndrome Differentiation Scale (SDSVD) score], vascular endothelial function [NO, endothelin 1 (ET-1)], oxidative stress [lipid peroxide (LPO), superoxide dismutase (SOD), C Dialdehyde (MDA)], endoplasmic reticulum stress response (Hcy, CRP) related indicators before and after treatment in three groups. Results showed that the total effective rate of treatment in the study group was higher than that in the control groups A and B, the difference was statistically significant (p<0.05). In symptom improvement, the MoCA score of the study group was higher than that of the control groups A and B after the treatment course, and the SDSVD score was lower than that of the control groups A and B (p<0.05); In the vascular endothelial function section, after the course of treatment, the serum NO level in the study group was higher than that in the control groups A and B, and the ET-1 level was lower than that in the control groups A and B (p<0.05). In oxidative stress experiment, after the course of treatment in the study group, the serum LPO and MDA levels were lower than those in the control groups A and B, and the SOD levels were higher than those in the control groups A and B (p<0.05). Endoplasmic reticulum stress response results showed that after the course of treatment in the study group, the serum Hcy and CRP levels were lower than those in the control groups A and B (p<0.05). In adverse reactions section, there was no significant difference in the incidence of adverse reactions among the three groups (p>0.05). Dengzhan Shengmai Capsule combined with butylphthalide soft capsule is the first treatment for VD, with definite curative effect, which can effectively reduce the damage of vascular endothelial function and inhibit oxidative stress response, antagonize the endoplasmic reticulum stress response, thereby further alleviating dementia symptoms and improving cognitive function.